NMR-ON MEASUREMENTS OF I-123, I-124, I-131 IN NICKEL - Ohya, S; Muto, S; Katsurayama, M; Heiguchi, K; Mutsuro, N; Stone, N; Rikovska, J (Kluwer Academic Publishers, 1992)
The magnetic hyperfine splitting frequencies of123I Ni,124I Ni and131I Ni in a zero external magnetic field have been determined by the NMR-ON method as 258.9(1), 165.9(1) and 179.5(2) MHz, respectively. With the known values of the magnetic moments, the magnetic hyperfine fields have been deduced:BHF(123I Ni)=30.17(5) T, BHF(124I Ni)=30.14(9) T, BHF(131I Ni)=30.06(4) T; the weighted average is BHF(I Ni)=30.11(4) T. The small difference of the BHF(131I Ni) with those of123I Ni and124I Ni is discussed comparing with results of the hyperfine splitting frequency of iodine in iron host. © 1992 J.C. Baltzer A.G., Scientific Publishing Company.